Ultrasound assisted homing of human umbilical cord mesenchymal stem cells promotes recovery from acute respiratory distress syndrome - Bei-Ying Wang; Xiao Zhang; Ting-Tian Li; Wei-Wei Qin; Xiang Liu; Kong-Miao Lu; Li-Xin Sun; Wei Han (Stem Cell Research & Therapy)
Abstract Background Human umbilical cord mesenchymal stem cells (hUC-MSCs) show potential for treating acute respiratory distress syndrome (ARDS), however, their homing to the lungs and survival time are insufficient. In this study, we evaluated whether pulsed focus ultrasound (pFUS) could promote the homing and prolonged retention of hUC-MSCs in the lungs of ARDS mice and explored the mechanisms involved. Methods Mice were divided into four groups: the NC group, the LPS group, the MSCs group, and the pFUS + MSCs group. Except for the NC group, the other three groups were constructed as ARDS models and given PBS, MSCs and pFUS + MSCs interventions. hUC-MSCs were used to assess lung tissue injury by HE staining, inflammatory cell count in alveolar lavage fluid (BALF), and expression of Tnf, Il1b and Il6 in the lung tissues; and apoptosis and proliferation in the lung tissues were assessed by TUNEL and immunofluorescence. Bioluminescence imaging was used to detect the homing rate and survival of hUC-MSCs in mouse lungs from 1 to 7 days. Cxcl5 and Igf1 was found to be differentially expressed and highly enriched by mRNA sequencing in MSC and sonicated groups and verified by PCR combined with ELISA. Results Compared with the LPS group, the lung inflammatory infiltrate and lung tissue damage in the MSCs group and pFUS + MSC group were alleviated, the number of inflammatory cells in the BALF and the expression of Tnf, Il1b and Il6 in the lung tissues were reduced, the expression of TUNEL-positive cells was reduced, and the expression of PCNA-positive cells was increased, and the decrease or increase was more significant in the pFUS + MSC group (P < 0.05). pFUS increased the number of hUC-MSCs homing in the lungs and prolonged lung survival to day 6 and significantly up-regulated lung tissue levels of SDF-1, ICAM-1, CXCL5 and IGF-1 compared to the MSCs group (P < 0.05). Conclusions pFUS preconditioning may improve lung homing and prolong survival of hUC-MSCs by upregulating the levels of homing-associated factors SDF-1, ICAM-1, CXCL5 and IGF-1, which in turn improves ARDS.